Risk Factors Associated With Disabilities In Morbus Hansen Patient - Annisa Tri Srilistiany; Dian Amelia Abdi; Solecha Setiawati (Sean Institute, 2023)
Morbus Hansen, or better known as leprosy, is an infectious disease that can cause various serious complications, including disability. This study aims to identify risk factors associated with the incidence of disability in Morbus Hansen patients. The research was carried out by collecting data from various sources, research journals conducted previously. The research results show that the risk factors that play a role in the incidence of disability in Morbus Hansen patients include the severity of the disease, delays in diagnosis and treatment, as well as socio-economic factors that influence patient access to medical care. These results have important implications for efforts to prevent and manage Hansen's Morbus, emphasizing the importance of early diagnosis, accessibility of treatment, and special attention to patients with more severe disease.